Past Trends in Student Personnel Services for Adults in Higher Education - Kuder, James M.; Colorado State Univ., Ft. Collins ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
An overview of past developments and trends which have had an impact on what is occurring at the present time in student personnel services for adults is presented. The intent was to establish some basis for current and future trends. The author contends that the development of student personnel services for adults in higher education has been extremely painful, erratic, and slow and that there now seems to be a major trend that these services be handled by specially trained personnel. Particular attention is given to the areas of admissions, financial aid, counseling, housing and food service and veterans affairs. (TA)
Educational level discussed: Adult Education.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Adult Programs; Educational Development; Educational Trends; Higher Education; Student Personnel Services